Preventing violence against refugee adolescent girls: findings from a cluster randomised controlled trial in Ethiopia - Stark, Lindsay (BMJ Glob Health, 2018)
INTRODUCTION: Interpersonal violence is a critical public health concern in humanitarian contexts, but evidence of effective violence prevention programmes targeting adolescent girls is lacking. We investigated the efficacy of a life skills and safe spaces programme to reduce adolescent girls’ experiences of interpersonal violence in a refugee setting. METHODS: In this two-arm, single-blinded, cluster randomised controlled trial, we recruited 919 Sudanese and South Sudanese girls ages 13–19 years residing in refugee camps in Ethiopia. Girls were divided into 31 clusters, with 457 and 462 participants assigned to the intervention and control arms, respectively. Intervention clusters received 30 life skills sessions delivered in safe spaces and 8 complementary sessions for caregivers. The primary outcome was exposure to sexual violence in the previous 12 months. Secondary outcomes included disaggregated forms of sexual violence, physical violence, emotional violence, transactional sex, child marriage, feelings of safety, attitudes around rites of passage and perceptions of social support. Intent-to-treat analysis was used. RESULTS: At 12-month follow-up, the intervention was not significantly associated with reduction in exposure to sexual violence (adjusted OR =0.96, 95%  CI 0.59 to 1.57), other forms of violence, transactional sex or feelings of safety. The intervention was associated with improvements in attitudes around rites of passage and identified social supports. Additionally, the intervention showed a decrease in reported child marriage among girls who were married at baseline. CONCLUSION: While the intervention impacted key markers along the causal pathway to violence reduction, further research and programmatic adaptations are needed to prevent violence towards adolescents in humanitarian contexts. TRIAL REGISTRATION: NCT02506543.